TI_GERICHTE 17.2008.66 vom 30. Dezember 2008 , Furto con scasso. Ricettazione di armi. Confisca. Commisurazione della pena - TI Tribunale d'appello (2008)
Furto con scasso. Ricettazione di armi. Confisca. Commisurazione della pena